2013
DOI: 10.1145/2528400
|View full text |Cite
|
Sign up to set email alerts
|

The complexity of the counting constraint satisfaction problem

Abstract: The Counting Constraint Satisfaction Problem (#CSP(H)) over a finite relational structure H can be expressed as follows: given a relational structure G over the same vocabulary, determine the number of homomorphisms from

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(21 citation statements)
references
References 60 publications
0
21
0
Order By: Relevance
“…Although it is not known if there is a dichotomy for CSP, Bulatov has recently shown that, for every Γ , #CSP(Γ ) is either computable in polynomial time or #P-complete [4]. Two of the present authors have since given an elementary proof of this result and also shown the dichotomy to be decidable [24].…”
Section: Counting Cspmentioning
confidence: 64%
See 1 more Smart Citation
“…Although it is not known if there is a dichotomy for CSP, Bulatov has recently shown that, for every Γ , #CSP(Γ ) is either computable in polynomial time or #P-complete [4]. Two of the present authors have since given an elementary proof of this result and also shown the dichotomy to be decidable [24].…”
Section: Counting Cspmentioning
confidence: 64%
“…This should not be confused with the concept of primitive positive definability (pp-definability) which appears in algebraic treatments of CSP and #CSP, for example in the work of Bulatov[4].…”
mentioning
confidence: 99%
“…It is again the polymorphisms of a language which determine tractability of #CSP( ). Bulatov has characterised all languages for which #CSP( ) can be solved in polynomial time and proved that for all other languages the problem is #P-complete [26]. All tractable languages have a Mal'tsev polymorphism.…”
Section: Quantified Csp Uncertain Csp #Csp and Related Problemsmentioning
confidence: 99%
“…The complexity of the exact counting problem (when we are required to find the exact number of solutions) is settled in [6] by showing that for any finite D and any set Γ of relations over D the problem is polynomial time solvable or is complete in a natural complexity class #P . One of the key steps in that line of research is the following result: For a relation R and a set of relations Γ over D, such that R belongs to the co-clone generated by Γ, then #CSP(Γ ∪ {R}) is polynomial time reducible to #CSP(Γ).…”
Section: Max-quantifiersmentioning
confidence: 99%
“…For the decision problem, a number of very strong results have been proved using methods of universal algebra [1], [4], [5], [9], [15]. For the exact counting CSP a complete complexity classification of such problems has been obtained [6]. Substantial progress has been also made in the quantified CSP [10].…”
Section: Introductionmentioning
confidence: 99%